INCIDENTAL ATHEROSCLEROSIS IN SUDDEN DEATH CASES BROUGHT TO MORTUARY CIVIL HOSPITAL AHMEDABAD - Garg, Surbhee; Dewangan, Tikendra; Chaudhari, Nishith; Shah, Kalpesh. A; Tandon, RN (Journal of Forensic Medicine and Toxicology, 2019)
Autopsy is the examination of a person’s body after his death1.1. It is essential part of death investigation. Medico legal autopsy deals not only with unnatural deaths, but also with large areas of deaths from natural causes. Most of them are sudden, unexpected and clinically incomprehensible. Death is said to be sudden or unexpected when a person not known to have been suffering from any dangerous disease, injury or poisoning is found dead or dies within 24 hours after the onset of terminal illness.1.2 Coronary atherosclerosis sometimes called as ‘the Captain of the Men of Death’, is the most frequent cause of sudden death in Western societies.1.3In cases of Sudden Deaths, the goal of the clinical autopsy is to determine whether death was due to cardiac disease or one of the many non-cardiac causes. The clinical autopsy generally includes histology. Modified Verbal Autopsy questionnaire based on medical records and by interview of family members and police aids in determining cause of death.This study was conducted from 1st January 2017 to 30th June 2017 at Post-Mortem Room, Forensic Medicine Department and at Autopsy laboratory under Department
Keywords: Young; sudden deaths; clinical autopsy; coronary atherosclerosis; Modified Verbal Autopsy